Making decisions - Russo, J. Edward (Henry Stewart Talks, 2011)
Decision process versus decision outcome, Decision + Execution + Chance = Results, Four phases of a good decision process, Framing: a mental structure to simplify the problem, Frame skills, Frame change, Frame control, Gathering intelligence, Avoiding information distortion and the confirmation bias, Coming to conclusions, Pyramid of approaches, Learning from experience, Experience is what happened, learning is why it happened, Lessons learned analyses
Reviewed at 2016/06/30